2012
DOI: 10.1097/nmc.0b013e31824239ce
|View full text |Cite
|
Sign up to set email alerts
|

Treating Polycystic Ovary Syndrome and Infertility

Abstract: Between 4% and 18% of women worldwide are affected by polycystic ovary syndrome (PCOS) and have the hormonal imbalances that lead to the cascade of symptoms, including weight gain and obesity. One of the first suggested treatments for infertility associated with PCOS is weight reduction, which has been shown to increase the chance of spontaneous ovulation and menstruation. Pharmacologic treatment usually includes metformin alone or in conjunction with clomiphene; both have been shown to increase conception rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…As 4-18% of the women suffer from polycystic ovarian syndrome and lack of hormonal balance (as one of the important causes of infertility), which are accompanied with overweight and obesity, the first recommendation and intervention to treat infertility is losing weight which increases the chance of ovulation and consequently spontaneous pregnancy. [21] Researchers have shown that overweight and obesity in women lead to increase of infertility risk, maternal and fetal complications. [222324] Other studies have also shown the importance of fixing the diet and weight in individuals undergoing infertility treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As 4-18% of the women suffer from polycystic ovarian syndrome and lack of hormonal balance (as one of the important causes of infertility), which are accompanied with overweight and obesity, the first recommendation and intervention to treat infertility is losing weight which increases the chance of ovulation and consequently spontaneous pregnancy. [21] Researchers have shown that overweight and obesity in women lead to increase of infertility risk, maternal and fetal complications. [222324] Other studies have also shown the importance of fixing the diet and weight in individuals undergoing infertility treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Women with PCOS have higher rates of endometrial cancer, cardiovascular disease, dyslipidemia and Type II diabetes mellitus. 4 Patients with PCOS having a greater prevalence of atherosclerosis and cardiovascular disease, benefited from calorie restriction even if it is not accompanied by weight loss. [5][6][7] Low dose combined oral contraceptive pill act to cause reduction of LH secretion, inhibition of ovarian and adrenal androgen production and reduction of the free testosterone fraction secondary to increased SHBG production in liver.…”
Section: Introductionmentioning
confidence: 99%
“…15 It is nonsteroidal selective estrogen receptor modulator. 16 It is usually given in 5 mg oral tablet for 5 consecutive day start from day (2)(3)(4)(5)(6) or (5)(6)(7)(8)(9). Gonadotropin to be used in clomiphene resistant/failure.…”
Section: Introductionmentioning
confidence: 99%
“…Women with PCOS are predisposed to higher rates of cardiovascular disease, obesity, dyslipidemia, hypertension, impaired glucose tolerance, type 2 diabetes mellitus, and endometrial cancer . Cardiovascular disease is of concern for both women and men as it is the leading cause of mortality in the United States .…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Women with PCOS are predisposed to higher rates of cardiovascular disease, obesity, dyslipidemia, hypertension, impaired glucose tolerance, type 2 diabetes mellitus, and endometrial cancer. 1,6 Cardiovascular disease is of concern for both women and men as it is the leading cause of mortality in the United States. 7 In addition, women with PCOS are reported to have surrogate markers of vascular diseases, such as impaired endothelial function and increased carotid artery intima-media thickness.…”
Section: Introductionmentioning
confidence: 99%